If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + 7 = 44 Reorder the terms: 7 + z = 44 Solving 7 + z = 44 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + z = 44 + -7 Combine like terms: 7 + -7 = 0 0 + z = 44 + -7 z = 44 + -7 Combine like terms: 44 + -7 = 37 z = 37 Simplifying z = 37
| 8v+28=-3(v-2) | | 19-c=4 | | -7(k+3)-(-8k+7)=5 | | 2+3x-5x=-4 | | 16(x-9)=4(2a-x) | | -6(u+6)=4u+4 | | 1/4t+3/5=2/5-t | | -7x+3-5x=-57 | | 8+28m-24-12m=0 | | -34=5x+3(x+2) | | f(x)=a(x+3)(x+1)(x-4) | | 5y-7x=12 | | 6x^2+3xy+3y^2=108 | | x=-1.5+0.5y | | -3t^2+16t-11=0 | | 16x^2+64t+64=0 | | 6-2x(3-12)=2x+90 | | 20x+5=-2x | | 3(u-5)-6u=-33 | | 0.4-8.1y-2.7y=1-10.8y-0.6 | | 11(k-2)+[k-3(k+1)]=0 | | (3c-8)(3c-8)=0 | | y=-3+2y | | 7(y+2)-5y=-4 | | 8-28m-24-12m=0 | | 2(t-1)+3t=2 | | -2(d+6)=-20 | | 2*j=25+j | | K-(-40)=32 | | 2t-4=2 | | 36=4(8x+1) | | 3(w+7)=-3 |